2014
DOI: 10.1111/jch.12370
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Components of Arterial Pressure Among Older Individuals (the Multinational MEDIS Study): The Role of the Mediterranean Diet and Alcohol Consumption

Abstract: The aim of this work was to evaluate factors associated with arterial blood pressure in a sample of older Mediterranean people without known cardiovascular disease. During 2005 to 2011, 2813 older (aged 65–100 years) individuals from 22 Mediterranean islands and the rural Mani region (Peloponnesus) voluntarily enrolled. Standard procedures were used to determine arterial BP and pulse pressure and for the evaluation of dietary habits (including tea and alcoholic beverages consumption), lifestyle, and anthropome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…It is important to note that the present study did not consider clinical data but only information directly declared by the volunteers. Despite this, a negative association was found between hypertension prevalence and fulfillment of the MD, in agreement with recent reports [25,28]. However, no relationship was reported between other risk factors (obesity, diabetes, dyslipidemia, and smoking) and MD compliance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is important to note that the present study did not consider clinical data but only information directly declared by the volunteers. Despite this, a negative association was found between hypertension prevalence and fulfillment of the MD, in agreement with recent reports [25,28]. However, no relationship was reported between other risk factors (obesity, diabetes, dyslipidemia, and smoking) and MD compliance.…”
Section: Discussionsupporting
confidence: 90%
“…There is a wealth of evidence that supports the inverse association between following the MD and the prevalence of coronary heart disease and hypertension [24,25,26,27]. It is important to note that the present study did not consider clinical data but only information directly declared by the volunteers.…”
Section: Discussionmentioning
confidence: 91%
“…35 kg/ m 2 as compared to those with normal BMI. This finding is in accordance with previous studies that reported strong associations between high BMI levels, hypertension, and high PP in middle-aged and older populations [27]. Obesity in older adults remain a complex concept [28], due to the probable decline in the added risk for hypertension with ageing, and the paradoxical consequences of excess weight for hypertensive health among the elders [28,29].…”
Section: Discussionsupporting
confidence: 93%
“…An inverse association between light alcohol consumption and arterial stiffness is well-documented in the general population. [27][28][29] Many studies suggested that light-moderate, non-binge consumption of alcoholic beverages, especially red wine, significantly reduces the risk of coronary heart disease. Laboratory experiments have shown that moderate alcohol consumption promotes anti-inflammatory processes along with several other proposed mechanisms that may induce cardioprotection.…”
Section: Discussionmentioning
confidence: 99%